Influência de fatores ambientais sobre a distribuição e abundância de anuros na Amazônia Meridional - Velasquez, Carla Lopes (2011)
Studies about the distribution of anurans are often carried out in aquatic environments, what minimizes the understanding of structures and processes that shape the distribution of anuran species, mainly terrestrials. Species of the Pristimantis (Strabomantidae) and Leptodactylus (Leptodactylidae) genus, such as L.andreae, and a few from the Pentadactylus group, are usually abundant and well-distributed in terrestrial environments in the Amazon rainforest, although there is still a lot of controversy over the factors that might influence the distribution and abundance of these species. This study analyzes the effect of environmental factors (temperature, relative air humidity ranges, canopy openness, leaf- litter volume, sand and clay proportion of the soil, its pH, distance between plots and streams, number of trees and after-logging interval) in the distribution and abundance of anuran species in the Meridional Amazon rainforest. Data was collected in 31 plots, divided into three areas in the city of Claudia, MT, Brazil. A total of 12 species belonging to four families were registered. Pristimantis cf. fenestratus was the most abundant specie, with 279 individuals found in 25 plots, Leptodactylus andreae was the second most abundant specie with 32 individuals distributed in 12 plots, and L. paraensis the least abundant (21 individuals), found in 11 of the 32 plots. The abundance of Pristimantis cf. fenestratus was negatively influenced by the clay proportion and after-logging interval. Relative air humidity was the only factor to affect the distribution of L. paraensis and none of the studied factors influenced the distribution of Leptodactylus andreae. Our results show that even anurans with similar reproductive modes can be affected by different environmental factors, and that species which are more sensitive to anthropic alterations can be affected by the recovery interval after an environmental disturbance.